Inhomogeneous Cortical Synchronization and Partial Epileptic Seizures - Vega-Zelaya, Lorena; Pastor, Jesús Eduardo; de Sola, Rafael G.; Ortega, Guillermo J. (Frontiers in Neurology, 2014)
Objective: Interictal synchronization clusters have recently been described in several publications using diverse techniques, including neurophysiological recordings and fMRI, in patients suffering from epilepsy. However, little is known about the role of these hyper-synchronous areas during seizures. In this work, we report an analysis of synchronization clusters jointly with several network measures during seizure activity; we then discuss our findings in the context of prior literature. Methods: Subdural activity was recorded by electrocorticography (with sixty electrodes placed at temporal and parietal lobe locations) in a patient with temporal lobe epilepsy with partial seizures with and without secondary generalization. Both interictal and ictal activities (during four seizures) were investigated and characterized using local synchronization and complex network methodology. The modularity, density of links, average clustering coefficient and average path lengths were calculated to obtain information about the dynamics of the global network. Functional connectivity changes during the seizures were compared with the time-evolution of highly synchronized areas. Results: Our findings reveal temporal changes in local synchronization areas during seizures and a tight relationship between the cortical locations of these areas and the patterns of their evolution over time. Seizure evolution and secondary generalization appear to be driven by two different underlying mechanisms.